2018
DOI: 10.15740/has/ijae/11.1/135-137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different land configuration on the yield of soybean (Glycine max L.)

Abstract: : A field experiment was conducted during the Kharif season of 2014-15, 2015-16 and 2016-17 at KVK, Indore to study the effect of different land configuration on the yield of soybean. The experiment consisted of three treatments of land configuration, viz., T 1 (FIRBS layout), T 2 (Ridge and furrow layout), T 3 (BBF layout), under RBD design with seven replications. Result showed that significant increase was observed in yield contributing characters viz., number of pods plant -1 , 100 seed weight (g), seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
1
Order By: Relevance
“…Consistently, Selvarajua et al (1999) also reported 17 % more soil moisture in BBF compare to FB. In contrasts to our findings, Singh et al (2018) reported 28.54 % soil moisture in RF and 27.58 % in BBF, nevertheless they similarly reported the least soil moisture in FB. The principal aim of land configuration are; the preparation of a conducive seedbed for seed germination and seedling growth, conservation of soil moisture that influences the infiltration characteristics of the soil, and also, provides adequate soil depth for optimum root growth and proper fertilizers placement.…”
Section: Influence Of Land Configuration On Soil Moisture Contentcontrasting
confidence: 99%
“…Consistently, Selvarajua et al (1999) also reported 17 % more soil moisture in BBF compare to FB. In contrasts to our findings, Singh et al (2018) reported 28.54 % soil moisture in RF and 27.58 % in BBF, nevertheless they similarly reported the least soil moisture in FB. The principal aim of land configuration are; the preparation of a conducive seedbed for seed germination and seedling growth, conservation of soil moisture that influences the infiltration characteristics of the soil, and also, provides adequate soil depth for optimum root growth and proper fertilizers placement.…”
Section: Influence Of Land Configuration On Soil Moisture Contentcontrasting
confidence: 99%
“…The higher uptake of micronutrients in coated treatments as compared to uncoated ones, might be attributed to the coatings of DAP and RP reduced the fixation of various nutrients and reduced the dissolution rate as well as surface area of contact with soil particles, which might have helped to increase availability of these nutrients throughout the growth periods of crop. Similar results were also reported by Singh,[17] andSanthi et al [10].…”
supporting
confidence: 92%